COMMUNITY POTENTIAL THROUGH UMKM EMPOWERMENT, HEALTH, AND INCREASING AWARENESS OF RELIGIOUS EDUCATION IN CICADAS VILLAGE, CIAMPEA DISTRICT, REGENCY - Sarifudin, Agus; Setiawan, Budi (STAI Al-Hidayah Bogor, 2024)
Education is one of the basic capital of development, so education is an investment (capital) in the future. The progress of Indonesian Islam is a desire for every Muslim to be free from all kinds of evils that occur. Both from the individual of every person and the Islamic society as a whole. This research uses a descriptive narrative method, with a method of presentation and describing the data. The results of this study are the realization of Qur'an reading guidance (iqra'), Qur'an tahsin guidance; have a fairly good level of understanding and awareness of religious practice; the existence of changes and developments in people's lives; received a positive response to the activities of the Academic Community from leaders and the community